2022
DOI: 10.7150/ijbs.69343
|View full text |Cite
|
Sign up to set email alerts
|

HB-EGF induces mitochondrial dysfunction via estrogen hypersecretion in granulosa cells dependent on cAMP-PKA-JNK/ERK-Ca2+-FOXO1 pathway

Abstract: Polycystic ovarian syndrome (PCOS) is one of the most prevalent endocrinopathies and the leading cause of anovulatory infertility, but its pathogenesis remains elusive. Although HB-EGF is involved in ovarian cancer progression, there is still no clarity about its relevance with PCOS. The present study exhibited that abundant HB-EGF was noted in follicular fluid from PCOS women, where it might induce the granulosa cells (GCs) production of more estrogen via the elevation of CYP19A1 expression after binding to E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…In patients without implantation, the follicular fluid HB-EGF levels are 230 pg/mL [30]. However, a recent study shows that the follicular fluid HB-EGF levels in IVF patients without polycystic ovarian syndrome (PCOS) are around 3 ng/ mL, which is 10-fold higher than the value reported by the study mentioned above [31]. Therefore, future studies will need to confirm the protein levels of HB-EGF in human follicular fluid.…”
Section: Discussionmentioning
confidence: 79%
“…In patients without implantation, the follicular fluid HB-EGF levels are 230 pg/mL [30]. However, a recent study shows that the follicular fluid HB-EGF levels in IVF patients without polycystic ovarian syndrome (PCOS) are around 3 ng/ mL, which is 10-fold higher than the value reported by the study mentioned above [31]. Therefore, future studies will need to confirm the protein levels of HB-EGF in human follicular fluid.…”
Section: Discussionmentioning
confidence: 79%
“…LDHA overexpression led to a reduction of cells in the G0/G1 phase, while MK‐2206 eliminated this effect, arresting cells in the G0/G1 phase (Figure 5D,E). To further examine the effect of FOXO1 on trophoblast proliferation, we treated HTR‐8 cells with 10 μM of FOXO1 inhibitor AS1842856 for 24 h. The AS1842856 could inhibit the activity of FOXO1 by binding with it 23–25 . As the FOXO1 activity was inhibited, more HTR‐8 cells entered the S phase from the G0/G1 phase (Figure S3A,B) and expressed higher CyclinD1 (Figure S3C,D).…”
Section: Resultsmentioning
confidence: 99%
“…To further examine the effect of FOXO1 on trophoblast proliferation, we treated HTR-8 cells with 10 μM of FOXO1 inhibitor AS1842856 for 24 h. The AS1842856 could inhibit the activity of FOXO1 by binding with it. [23][24][25] As the FOXO1 activity was inhibited, more HTR-8 cells entered the S phase from the G0/G1 phase (Figure S3A,B) and expressed higher CyclinD1 (Figure S3C,D). Together, these findings in vitro suggest that LDHA regulates the trophoblast cell cycle via the PI3K/AKT/FOXO1 pathway, and the effect was related to Cyclin D1 and CDK4 protein modulation.…”
Section: Ldha-regulated Trophoblast Proliferation Via the Pi3k/akt Si...mentioning
confidence: 99%
“…A recent study showed that copious amounts of HB-EGF are present in the follicular fluid in PCOS. It is suggested that the presence of abundant HB-EGF in the fluid may bring about estrogen hypersecretion through the JNK/ERK pathway, resulting in apoptosis of granulosa cells and mitochondrial dysfunction [ 65 ]. As estrogen is considered to be an androgen, the influence of HB-EGF on the JNK/ERK pathway may be another contributor to hyperandrogenism in PCOS.…”
Section: The Effect Of Androgens On Signaling Pathways In Pcosmentioning
confidence: 99%